ENERGY CONVERSION IN THE PRAWN METAPENAEUS DOBSONI (MIERS) FED ON ARTIFICIAL FEED - Thomas, M M; Easterson, D C V; Kathirvel, M (Indian Journal of Fisheries, 2011)
Measured quantities of feed containing 33.33% by weight of tapiocapowder, 16.67% of rice bran, 41.67% of fishmeal and 8.33% of mineral supplements(Starmin PS), made into pellets, using agar-agar as binding agent, werefed to Metapenaeiis dobsoni. Mean gross and net conversion (growth) efficiencies,Ki and : 2. were; 39.62% and 49.34%. Average assimilation efHciency was ofthe order 80.99%.